2015
DOI: 10.5194/bg-12-5667-2015
|View full text |Cite
|
Sign up to set email alerts
|

Does <i>Juncus effusus</i> enhance methane emissions from grazed pastures on peat?

Abstract: Abstract. Methane (CH 4 ) emissions from drained organic soils are generally low, but internal gas transport in aerenchymatous plants may result in local emission hotspots. In a paired-sample field study at three different sites we measured fluxes of CH 4 with static chambers from adjacent sampling quadrats with and without Juncus effusus during four field campaigns. At all three sites, CH 4 was observed in the soil at all sampling depths (5 to 100 cm), and in most cases both above and below the groundwater ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As discussed earlier, vascular plants can play an important role in transporting CH 4 from soils to the atmosphere through aerenchyma (Couwenberg & Fritz, ; Henneberg, Elsgaard, Sorrell, Brix, & Petersen, ). The establishment of vascular vegetation following extraction is generally more extensive on cutover fens than on cutover bogs (Graf, Rochefort, & Poulin, ).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, vascular plants can play an important role in transporting CH 4 from soils to the atmosphere through aerenchyma (Couwenberg & Fritz, ; Henneberg, Elsgaard, Sorrell, Brix, & Petersen, ). The establishment of vascular vegetation following extraction is generally more extensive on cutover fens than on cutover bogs (Graf, Rochefort, & Poulin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant functional groups differ in their ability to transport CH 4 with graminoids exhibiting greater internal CH 4 transport than forbs (Bhullar et al, ). At our study site, Juncus effusus (Juncus), a graminoid, is more dominant in improved/grazed wetlands than seminative wetlands (Boughton, Quintana‐ascencio, & Bohlen, ; Ervin & Wetzel, ; Gathumbi et al, ; Tweel & Bohlen, ) and is known to transport CH 4 through plant‐mediated transport directly from the production site to the atmosphere (Dalal et al, ; Henneberg et al, ; Henneberg et al, ; Petersen et al, ; Ström et al, ). While juncus is dominant in the improved and grazed wetlands, it is neither clear which species it may be replacing nor whether it can explain the higher CH 4 emissions from these wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…Low emissions from organic grasslands would be expected due to the low water table and organic matter content (Tiemeyer et al, 2016), and emissions will be further mitigated by low CH 4 diffusion due to drainage-induced increases in soil bulk density (Nykänen et al, 1998). The observed emissions could be due to CH 4 transport through aerenchymatous tissue in Juncus plants (Henneberg et al, 2012); Juncus clumps have sometimes been observed to act as point-source emissions of CH in drained peatlands (Henneberg et al, 2015). Equally, the presence of Juncus may simply indicate that these collars were situated in wetter areas of the site where CH 4 emissions were more likely to occur.…”
Section: Co 2 and Ch 4 Fluxesmentioning
confidence: 99%
“…large amounts of biomass removal could counteract a terrestrial CO 2 sink and result in a C source (Renou- . However, methane (CH 4 ) can still be emitted by drained soils (Hendriks et al, 2007, Henneberg et al, 2015, with implications for C and GHG budgets.…”
Section: Introductionmentioning
confidence: 99%